An Event Study of Perindopril (Servier) Reverse Payment Patent Settlements’ Case: Is Krka Truly an Exception Within the Pay-For-Delay Commission Decision? - Ocepek, France (LeXonomica, 2023)
The article aims to fill the gap in the literature on reverse payment patent settlements between patent-holders and generic pharmaceutical firms in EU competition law. Based on the event study of the Perindopril (Servier) case of the European Commission, the research provides a novel assessment of the welfare effects of Commission enforcement and the following judiciary decision on the legality of Commission sanctions. Within the case, the analysis paid particular attention to the generic corporation Krka because Commission fined Krka for the settlement with Servier that did not include the reverse payment, and the Commission decision did not survive the scrutiny of the General Court. The relative economic power of Krka in the perindopril market is also a factor that, together with the enforcement effect assessment, provides a different perspective of the event study’s normative implications to the existing research. Povzetek Namen članka je zapolniti vrzel v literaturi o poravnavah v zvezi s povratnimi plačili med imetniki patentov in generičnimi farmacevtskimi podjetji na področju konkurenčnega prava EU. Raziskava temelji na študiji dogodka v zadevi Evropske komisije Perindopril (Servier) in zagotavlja novo oceno učinkov izvrševanja s strani Komisije na blaginjo in naknadne sodne odločitve o zakonitosti sankcij Komisije. V okviru primera je analiza posebno pozornost namenila generični korporaciji Krka, saj je Komisija naložila globo družbi Krka zaradi poravnave s podjetjem Servier, ki ni vključevala povratnega plačila, odločitev Komisije pa ni prestala presoje Splošnega sodišča. Relativna gospodarska moč družbe Krka na trgu perindoprila je prav tako dejavnik, ki skupaj z oceno učinka izvrševanja zagotavlja drugačen pogled na normativne posledice študije dogodka v primerjavi z obstoječimi raziskavami.